THE HISTORY OF THE DEVELOPMENT OF PENCIL DRAWING - Turdaliyeva Dildora; Xojimatov Adhamjon G`afurjon o`g`li (American Journals, 2023)
Primitive community system is one of the earliest and longest stages in the history of human development. All nations and peoples have experienced this stage. In this long process of development, the modern type of man appeared, a community of people was created. From the system of the primitive community to us, the material evidence of work and hunting tools, household items and ornaments, and the remains of places where people lived have reached us.
Keywords: pencil drawing, draft, stone age, copper and bronze age, iron age, original copy, print, vertical, horizontal, estamp.